Optimalisasi Teknik Pembukaan Lahan dalam Mendukung Keberlanjutan Pertanian di Wilayah Tropis: Studi Kasus Desa Dahana Tabaloho - Lilis Sartika Gulo; Nofianti Zebua; Julfan Solala Zebua; Diferman Gulo; Natalia Kristiani Lase (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
This research aims to explore the optimization of land clearing techniques in supporting agricultural sustainability in Dahana Tabaloho Village, Gunungsitoli District, North Sumatra. This research involved students of the University of Nias Agrotechnology Study Program who applied land clearing techniques which included weed removal, soil loosening, drainage and bed making. The methods used in this study were direct observation, interviews, and measurement of soil parameters before and after the application of the techniques. The results showed that the combination of traditional and modern techniques in land management can improve tillage efficiency and environmental sustainability. The use of cultivators for soil loosening is proven to speed up the process, but still requires organic fertilizer to maintain the quality of the soil structure. Good drainage is effective in managing excess water and ensuring water availability during the dry season. In addition, making beds with proper direction supports optimal plant growth. The 15% increase in organic matter content and the stability of soil pH to remain neutral are indicators of the success of the applied techniques. Overall, this study provides evidence that proper land management can support sustainable agricultural productivity in the tropics.